2021
DOI: 10.3389/fnut.2021.769223
|View full text |Cite
|
Sign up to set email alerts
|

Skimmed Bovine Milk-Derived Extracellular Vesicles Isolated via “Salting-Out”: Characterizations and Potential Functions as Nanocarriers

Abstract: Bovine milk-derived extracellular vesicles (BM-EVs) are recognized as promising nanoscale delivery vectors owing to their large availability. However, few isolation methods can achieve high purity and yield simultaneously. Therefore, we developed a novel and cost-effective procedure to separate BM-EVs via “salting-out.” First, BM-EVs were isolated from skimmed milk using ammonium sulfate. The majority of BM-EVs were precipitated between 30 and 40% saturation and 34% had a relatively augmented purity. The separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In such cases, some published studies use precipitation‐based methods, such as ExoQuick ® and ExoEasy ® (Bickmore & Miklavcic, 2020 ; Kupsco et al., 2021 ; Soares Martins et al., 2018 ). Although these methods are efficient, they can result in co‐isolation of non‐EV proteins (Lobb et al., 2015 ; Tan et al., 2021 ; Wijenayake et al., 2021 ; Zlotogorski‐Hurvitz et al., 2015 ). Additionally, EV fractions obtained from ExoQuick ® may contain traces of biopolymers that can interfere with mass spectrometry (Taylor & Shah, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, some published studies use precipitation‐based methods, such as ExoQuick ® and ExoEasy ® (Bickmore & Miklavcic, 2020 ; Kupsco et al., 2021 ; Soares Martins et al., 2018 ). Although these methods are efficient, they can result in co‐isolation of non‐EV proteins (Lobb et al., 2015 ; Tan et al., 2021 ; Wijenayake et al., 2021 ; Zlotogorski‐Hurvitz et al., 2015 ). Additionally, EV fractions obtained from ExoQuick ® may contain traces of biopolymers that can interfere with mass spectrometry (Taylor & Shah, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, some published studies use precipitation-based methods, such as ExoQuick ® and ExoEasy ® (82)(83)(84). Although these methods are efficient, they can result in co-isolation of non-EV proteins (85)(86)(87)(88). Additionally, EV fractions obtained from ExoQuick ® may contain traces of biopolymers that can interfere with mass spectrometry (89).…”
Section: Discussionmentioning
confidence: 99%
“…However, several obstacles restrict its further clinical translation, including poor aqueous solubility, low membrane permeability, and obvious efflux from cells. Bovine milk-derived extracellular vesicles are recognized as promising nanoscale delivery to resolve this problem ( Tan et al, 2021 ). In conclusion, we demonstrated that ICA Ⅱ has protective effects and can rescue HUVECs from injury and dysfunction caused by PA in vitro via the SRPK1-Akt-eNOS signaling pathway.…”
Section: Discussionmentioning
confidence: 99%